An Electromagnetic System for Inducing a Localized Force Gradient in an ECM and Its Influence on HMVEC Sprouting. (February 2018) - See, Hian Hian; Herath, Sahan C. B.; Arayanarakool, Rerngchai; Du, Yue; Tan, Evan; Ge, Ruowen; Asada, Harry; Chen, Peter C. Y.
Mechanical properties of the extracellular matrix (ECM) have been observed to influence the behavior of cells. Investigations on such an influence commonly rely on using soluble cues to alter the global intrinsic ECM properties in order to study the subsequent response of cells. This article presents an electromagnetic system for inducing a localized force gradient in an ECM, and reports the experimentally observed effect of such a force gradient on in vitro angiogenic sprouting of human microvascular endothelial cells (HMVECs). This force gradient is realized through the induction of magnetic forces on the superparamagnetic microparticle–embedded ECM ( s ECM). Both analytical and statistically meaningful experimental results demonstrate the effectiveness of this approach in influencing the behavior of a targeted HMVEC sprout without affecting that of other sprouts nearby. These results suggest the possibility of selectively controlling the in vitro behavior of cells by the induction of a localized force gradient in the ECM.